Quantitative risk management in gas injection project: A case study from Oman oil and gas industry - Mohammad Miftaur Rahman Khan Khadem; Sujan Piya; Ahm Shamsuzzoha (Journal of Industrial Engineering International, 2018)
The purpose of this research was to study the recognition, application and quantification of the risks associated in managing projects. In this research, the management of risks in an oil and gas project is studied and implemented within a case company in Oman. In this study, at first, the qualitative data related to risks in the project were identified through field visits and extensive interviews. These data were then translated into numerical values based on the expert's opinion. Further, the numerical data were used as an input to Monte Carlo simulation. RiskyProject Professional™ software was used to simulate the system based on the identified risks. The simulation result predicted a delay of about 2 years as a worse case with no chance of meeting the project's on stream date. Also, it has predicted 8% chance of exceeding the total estimated budget. The result of numerical analysis from the proposed model is validated by comparing it with the result of qualitative analysis, which was obtained through discussion with various project managers of company.
Keywords: 650; Risk analysis; Quantitative analysis; Project management; Monte Carlo simulation